Large strain response in (1-x)(0.94Bi0.5Na0.5TiO3-0.06BaTiO3)-xSr0.8Bi0.1▫0.1Ti0.8Zr0.2O2.95 lead-free piezoelectric ceramics. Issue 2 (1st February 2019) - Li, Qiang; Ning, Li; Hu, Bin; Peng, Haijun; Zhao, Nianshun; Fan, Huiqing
Abstract: A series of novel lead-free (1- x )(0.94Bi0.5 Na0.5 TiO3 -0.06BaTiO3 )- x Sr0.8 Bi0.1 □0.1 Ti0.8 Zr0.2 O2.95 (SBTZ) ceramics were prepared via a traditional solid state sintering method. The ferroelectric, dielectric, AC impedance and fatigue properties were systematically studied. The introduction of VO and VA decreased the stability of ferroelectric phase, facilitated field-induced relaxor to ferroelectric transition and resulted in pinched and sloped P - E curves. The dielectric properties indicated that the relaxor phase of prepared ceramics was gradually dominated and the temperature of phase transition (TF-R ) went downwards to room temperature with the increase of SBTZ. Therefore, a giant unipolar strain of 0.494% with a normalized strain d33 * of 706 pm/V was obtained at x = 0.06. The AC impedance spectra of x = 0.06 ceramics revealed that its capacitance mechanism was derived from bulk effect. In addition, the stable fatigue resistance properties implied that the prepared ceramics were promising candidates for strain sensors and actuators.